Technochemical characteristic of organs and tissues of grey whale Eschrichtius robustus - Nickolay B. Ayushin; Ekatherina P. Karaulova; Lidia T. Kovekovdova; Konstantin G. Pavel; Alexander A. Popkov; Mikhail V. Simokon (Известия ТИНРО, 2017)
Chemical composition, content of protein, minerals, free amino acids and fatty acids in the muscles, heart, tongue, kidneys, liver, and lungs of California grey whale Eschrichtius robustus are examined. All eatable parts of the grey whale body are significantly watered (water content 78.5-80.5 %), with the minimum water content in the tongue and the maximum in the kidneys. The meat of grey whale has low lipid content and is similar to low-fat beef, lamb or horsemeat. All essential amino acids are presented in the proteins with slight differences in their content depending on localization. Lysine and leucine have the high level in all eatable parts of the whale (15.3-22.6 mg/g WW). The highest content of polyunsaturated fatty acids is found in the heart (36.49 %). The content of water-soluble protein varies from 17.9 % for the tongue to 57.9 % for the liver, the content of myofibrillar proteins in the meat, kidneys, tongue and heart ranges between 12.8-25.2 % but they are absent in the lungs and liver. Concentration of toxic elements (As and Cd) depends on localization, with the highest level in kidneys: As 0.42-2.80 mg/kg WW, Cd 0.05-1.22 mg/kg WW.